Adaptation to warmer climates by parallel functional evolution of CBF genes in Arabidopsis thaliana. Issue 15 (4th July 2016) - Monroe, J. Grey; McGovern, Cullen; Lasky, Jesse R.; Grogan, Kelsi; Beck, James; McKay, John K.
Abstract: The evolutionary processes and genetics underlying local adaptation at a specieswide level are largely unknown. Recent work has indicated that a frameshift mutation in a member of a family of transcription factors, C‐repeat binding factors or CBF s, underlies local adaptation and freezing tolerance divergence between two European populations of Arabidopsis thaliana . To ask whether the specieswide evolution of CBF genes in Arabidopsis is consistent with local adaptation, we surveyed CBF variation from 477 wild accessions collected across the species' range. We found that CBF sequence variation is strongly associated with winter temperature variables. Looking specifically at the minimum temperature experienced during the coldest month, we found that Arabidopsis from warmer climates exhibit a significant excess of nonsynonymous polymorphisms in CBF genes and revealed a CBF haplotype network whose structure points to multiple independent transitions to warmer climates. We also identified a number of newly described mutations of significant functional effect in CBF genes, similar to the frameshift mutation previously indicated to be locally adaptive in Italy, and find that they are significantly associated with warm winters. Lastly, we uncover relationships between climate and the position of significant functional effect mutations between and within CBF paralogs, suggesting variation in adaptive function of different mutations. Cumulatively, these findings support the hypothesis that disruption of CBF gene function is adaptive in warmer climates, and illustrate how parallel evolution in a transcription factor can underlie adaptation to climate.